Analysis of websites belonging to public universities from the perspective of the democratic governance exigencies. A marketing research approach - Corina RĂDULESCU; Oana Simona (Caraman) HUDEA; Răzvan Mihail PAPUC (Transylvanian Review of Administrative Sciences, 2018)
The Democratic Governance Model generates a visible opening of institutions towards citizens. By analyzing ten digital communication offers made by Romanian state universities, we pursue to observe if any partnership relationship with their users is created, if their websites are conceived so as to facilitate the participation of students in the activity of the institution, to comply with the manifested needs and to invite to dialogue. The result of the research reveals different degrees of ﬁdelity of the studied websites to the new management model.